THE ISSUES OF THE DEVELOPMENT STRATEGY FORMATION OF AVIATION INDUSTRY COMPANIES IN UKRAINE - Аrefieva Оlena; Miagkykh, Irina (Proceedings of National Aviation University (archive), 2016)
The article substantiates the notion of strategy, examines the issues of the formation and implementation of aviation company development strategy, and delineates the contingence of strategy formation upon internal and external factors influencing the long-term stability of companies’ business operation formation.